St. Mary's County Symbol AHX Aerial Photography Index (1938) (United STates Department of Agriculture, Agricultural Adjustment Administration, East Central Division, 1938)
4 photo sheets showing photo mosaic of aerial photograph sheets of St. Mary's County. Each tile has a number in the upper-right and represents a larger photograph that would be available for study (SMCHS does not have the detailed photographs).